The learning of general mathematical strategies: a developmental study of process attainments in mathematics, including the construction and investigation of a process-oriented curriculum for the first secondary year - Bell, A.W. (1976)
Consideration of the relative place of content and process in the mathematics curriculum leads to the following questions: 1. What is the nature of the mathematical process and how does it relate to the content? 2. Does the process comprise learnable strategies; if so, what are feasible learning objectives for different ages? 3. Can content and process be learned simultaneously or are there incompatibilities between effective teaching methods?